Blood Culture Contamination Creep Independent of COVID-19 Pandemics: An Interrupted Time-Series Analysis - Samo Jeverica; Jani Dernič; Peter Golob; Alenka Stepišnik; Bojan Novak; Tomaž Gantar; Lea Papst; Anamarija Juriševič Dodič; Darja Barlič Maganja; Jan Zmazek; Mladen Gasparini (Antibiotics)
Background/Objectives: Our study aimed to assess longitudinal trends in blood culture contamination in a regional secondary care teaching hospital before and after the COVID-19 pandemic and to evaluate differences in the interpretation of trends using two distinct quasi-experimental statistical methods, including interrupted time-series analysis. Methods: We analyzed data from a 10-year period spanning from 2015 to 2024, encompassing 147,733 admissions and 634,158 patient-days, as well as a total of 25,068 blood cultures. The (i) blood culture contamination rate, (ii) contaminant proportion, (iii) single blood culture rate, and (iv) first-to-second bottle contamination ratio were calculated. Results: The observed usage rate of blood cultures per 1000 patient-days was 38.9. The contamination rate of blood cultures increased from 0.9% to 1.5% (p = 0.001) in the post-COVID-19 period, accompanied by a rise in the proportion of contaminant bacteria from 9.8% to 14.2% (p = 0.016). Additionally, the proportion of single blood culture collections increased from 23.1% to 33.6% (p < 0.001). Finally, the overall first-to-second bottle contamination ratio was 1.54, while the ratio in the post-COVID-19 period was 1.92. Conclusions: In a low-COVID-19-burden secondary care teaching hospital setting, blood culture contamination rates have progressively increased over the past decade, irrespective of the pandemic. These findings underscore the importance of sustained vigilance in infection prevention and control practices, strict adherence to blood culture collection protocols, and the ongoing need for staff training.